2009
DOI: 10.15388/infedu.2009.08
|View full text |Cite
|
Sign up to set email alerts
|

Research into Cyberbullying: Student Perspectives on Cybersafe Learning Environments

Abstract: This paper reports a qualitative study designed to investigate the issues of cybersafety and cyberbullying and report how students are coping with them. Through discussion with 74 students, aged from 10 to 17, in focus groups divided into three age levels, data were gathered in three schools in Victoria, Australia, where few such studies had been set. Social networking sites and synchronous chat sites were found to be the places where cyberbullying most commonly occurred, with email and texting on mobile phone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
79

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(101 citation statements)
references
References 8 publications
0
22
0
79
Order By: Relevance
“…Seeking social support was another coping strategy reported by students in some research (Dehue et al, 2008; Kowalski et al, 2008; Mishna, Saini, & Solomon, 2009; Slonje & Smith, 2008; Smith, Mahdavi, et al). Although some students reported incidents of cyberbullying to friends or parents (Slonje & Smith; Smith, Mahdavi, et al; Stacey, 2009), researchers have suggested that when compared with victims of traditional bullying, victims of cyberbullying were less likely to seek help (Dehue et al; Li, 2006; Slonje & Smith). One possible reason was the fear that technology would be taken away (Kowalski et al; Stacey).…”
Section: High School Students’ Perceptions Of Coping With Cyberbullyingmentioning
confidence: 99%
See 1 more Smart Citation
“…Seeking social support was another coping strategy reported by students in some research (Dehue et al, 2008; Kowalski et al, 2008; Mishna, Saini, & Solomon, 2009; Slonje & Smith, 2008; Smith, Mahdavi, et al). Although some students reported incidents of cyberbullying to friends or parents (Slonje & Smith; Smith, Mahdavi, et al; Stacey, 2009), researchers have suggested that when compared with victims of traditional bullying, victims of cyberbullying were less likely to seek help (Dehue et al; Li, 2006; Slonje & Smith). One possible reason was the fear that technology would be taken away (Kowalski et al; Stacey).…”
Section: High School Students’ Perceptions Of Coping With Cyberbullyingmentioning
confidence: 99%
“…We have found a few published articles that used qualitative methodology to examine student perceptions of cyberbullying using focus group interviews to obtain information regarding experiences with cyberbullying (Agatston et al, 2007; Mishna et al, 2009; Spears, Slee, Owens, & Johnson, 2009; Stacey, 2009). Coping strategies such as deleting messages, seeking social support, and increasing security measures were discussed by these studies; however, coping was not the primary focus of the research questions.…”
Section: High School Students’ Perceptions Of Coping With Cyberbullyingmentioning
confidence: 99%
“…This social wonder is the thing that has come to be known as cyber bullying. As indicated by Stacey (2009) there are eight unique types of cyber bullying, which incorporate Blazing (on the web battles), Provocation (sending disgusting messages), Denigration (posting tattle), pantomime, trip (sharing people groups privileged insights), duplicity (deceiving somebody into sharing Mysteries), rejection, and cyber stalking.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Confronting the bully is commonly reported by adolescents if the victim knows the bully or is able to contact her or him (Aricak et al 2008;DiBasilio 2008;Stacey 2009). Although this strategy is often mentioned by those who experience victimisation, it has proved to be less helpful in retrospect (Price and Dalgleish 2010).…”
Section: Reactions Towards the Bullymentioning
confidence: 99%
“…Cyberspace specific coping strategies such as deleting or blocking threatening messages are generally used and considered to be helpful (Aricak et al 2008;Hinduja and Patchin 2007;Juvonen and Gross 2008;Kowalski, Limber, and Agatston 2008;Smith et al 2008;Stacey 2009). Price and Dalgleish (2010) found that blocking was the most used technical strategy and was also considered the most helpful online action exerted by the self-identified cybervictims.…”
Section: Technical Solutionsmentioning
confidence: 99%